Key problems of creating a central European payments union - VAN BRABANT, J.M. (PSL Quarterly Review, 2013)
The paper analyses the pros and cons of assisting Eastern European countries with some payment facility in their transition to market system over the next few years. The rationale underlying scheme, as well as the varied criticism such proposals have elicited are provided. The author presents the arguments for coming to grips with the prevailing and emerging external-payment constraints of the reforming countries, the original proposal for a payments facility, and some concrete data on what precisely will be involved in terms of capital commitments, credit facilities and behavioural constraints under international surveillance. JEL: P20, F33